From Cairo to the straits settlements: modern salafiyyah reformist ideas in Malay Peninsula - Zakariya, Hafiz (IIUM Press, 2007)
Early twentieth-century Malay Peninsula witnessed the emergence of Islamic reform movements. The Malay reformists who were discontented with the socio-economic and political conditions of the Malays criticised the Malay elites and called for “reformation” of their society. The Malay reformists derived inspirations for their reformist ideology from the leading Middle Eastern reformists, Muhammad 'Abduh, Rashid Rida and others, known as salafiyyah. Available data suggest that the transmission of salafiyyah ideas in particular, and Middle Eastern reformism in general, to Malay Peninsula were made possible by many factors. Of these factors, the roles of the haramayn, the centres of learning in Cairo and the invention of printing machines have been least explored. This study attempts to fill in the void in the existing literature.